Application and Prospective of CRISPR-Cas in Cancer Diagnosis and Therapy - Li, Xiaoshu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cancer, a leading cause of mortality worldwide, poses a significant challenge to public health. The advent of CRISPR-Cas systems has introduced a novel and promising approach to overcoming the limitations of conventional cancer therapies. This review delves into the burgeoning role of CRISPR-Cas in the oncology field, highlighting its utility in both cancer diagnosis and therapy. In the diagnostic realm, CRISPR-based technologies, such as DETECTR and SHERLOCK, leverage the non-specific collateral cleavage activity of Cas12 and Cas13 proteins for highly sensitive detection of nucleic acid sequences, offering rapid and sensitive diagnostic capabilities. Therapeutically, CRISPR-Cas systems inactivate oncogenes and enhance treatment outcomes through engineered variants and innovative approaches. Variants such as nCas9 and dCas9 have been engineered to enhance specificity and transcriptional regulation, respectively. Challenges including the need for high specificity to avoid off-target effects, long-term safety assessments and ethical considerations persist, yet ongoing research aims to refine these technologies for enhanced efficacy and safety. Overall, CRISPR-Cas systems herald a new era in precision medicine for cancer patients.